2008
DOI: 10.1111/j.1532-5415.2008.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Use of Bladder Anticholinergics and Cholinesterase Inhibitors: Long‐Term Functional and Cognitive Outcomes

Abstract: OBJECTIVES-To determine the cognitive and functional consequences of dual use of cholinesterase inhibitors (ChIs) and the bladder anticholinergics oxybutynin or tolterodine. DESIGN-Prospective cohort study.SETTING-Nursing homes (NHs) in the state of Indiana.PARTICIPANTS-Three thousand five hundred thirty-six Medicaid-eligible NH residents aged 65 and older taking a ChI between January 1, 2003, and December 31, 2004. Residents were excluded if they were taking an anticholinergic other than oxybutynin or toltero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 37 publications
(69 reference statements)
1
96
0
Order By: Relevance
“…The cholinesterase inhibitors, donepezil and rivastigmine, used to improve memory and consciousness in patients with Alzheimer's disease may theoretically interact with antimuscarinic drugs, though this does not appear to be a widespread problem. Case reports exist that document this interaction, but larger observational studies failed to note deterioration in mental status [79,80]. Thiazolidinediones frequently used in diabetic patients and gabapentin used in neuropathic pain can cause nocturia, and anticholinergic agents used in the treatment of Parkinson's disease may affect the evacuation of the bladder [81].…”
Section: Anticholinergic (Antimuscarinic) Drugsmentioning
confidence: 99%
“…The cholinesterase inhibitors, donepezil and rivastigmine, used to improve memory and consciousness in patients with Alzheimer's disease may theoretically interact with antimuscarinic drugs, though this does not appear to be a widespread problem. Case reports exist that document this interaction, but larger observational studies failed to note deterioration in mental status [79,80]. Thiazolidinediones frequently used in diabetic patients and gabapentin used in neuropathic pain can cause nocturia, and anticholinergic agents used in the treatment of Parkinson's disease may affect the evacuation of the bladder [81].…”
Section: Anticholinergic (Antimuscarinic) Drugsmentioning
confidence: 99%
“…While anticholinergic medications may alleviate OAB symptoms to a degree, the agents are not curative and are known to cause a constellation of antimuscarinic side-effects involving the central nervous system, eyes, and gastrointestinal tract [2][3][4]. The potential for side-effects and modest efficacy may contribute to the poor drug adherence observed with these agents [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For the elderly with AD prescribed Acetylcholinesterase Inhibitors (AChI) and anticholinergic agents in combination, Lu and Tune showed a significant worsening in MMSE after 2 years compared to those on AChI alone [40] Sink, et al found a 50% faster rate of functional decline in patients taking combination of AChI and anticholinergic agents (oxybutynin or tolterodine) compared to those on AChI alone, even though the ADAS-Cog scores were unchanged [41].…”
Section: Non-pharmacological Management Ui For the Elderly With Demenmentioning
confidence: 99%